Analysis of Shahpura Lake’s Water Quality, Madhya Pradesh, India - Salahuddin (Geography, Earth Science and Environment: Research Highlights Vol. 1, 2024)
Shahpura Lake is positioned in one of the opulent areas of Bhopal, the capital city of the state of Madhya Pradesh, India. The water of Shahpura Lake is polluted due to the substantial release of contaminated materials without acceptable treatment to expunge pernicious compounds. The present study is based on the Physico-Chemical Parameters of Shahpura Lake of Bhopal, Madhya Pradesh, India. Water samples were collected from five sampling stations namely Manisha Market (MM), Janki Nagar (JN), Manoria Care (MC), Bansal Hospital (BH) and Lalita Nagar (LN). The physico-chemical parameters such as Chloride (Cl), Total Hardness (TH), Alkalinity(A), pH(pH), Electric Conductivity (EC), Total Dissolved Solids (TDS), Fluoride(F), Iron (Fe), Turbidity (Td), Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and Sulphate (S) were examined to know the present status of the Lake water quality. Statistical analysis like Pearson Correlation matrix and Factor loadings were implemented to the data set to know the relationship among the studied parameters. Experimental data shows that most of the attributes do not satisfy the desirable limits prescribed by BIS. Hence the Shahpura Lake water is not suitable for drinking purposes.